Corporeality in Vera Pavlova’s poetry: about its sources - Sadzińska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The purpose of this article is an attempt to characterize the category of corporeality in the poetry by Vera Pavlova and to identify its sources. The analysis shows that this category is realized in different images and motifs, becoming the dominant poetics. In her works, the carnality is not limited to describing the man but it turns out to be an important, universal code that allows you to see the world in terms of unity and organicity. In this respect, Pavlova’s aesthetic exploration resembles the acmeist and – more distant – an ancient tradition.